The Dual of Generalized Fuzzy Subspaces - Wenjuan Chen; Yanyong Guan (Journal of Applied Mathematics)
We define the dual of generalized fuzzy subspaces first. These concepts generalize the dual of fuzzy subspaces. And then we investigate the double dual of generalized fuzzy subspaces.